Informations récentes sur la responsabilité des produits : partie 2 - Asselin, André (Assurances)

(untitled) (HEC Montréal, 1994)
In his attempts to bring the rules of product liability from craftsmanship to nuclear age, the New Civil Code of Quebec might have troubled quiet waters. ln the first part, the author reviewed the relevant sections of the New Code in that respect, and their roots in jurisprudence. He now examines the effects of the brand-new approach in the code to the rules of Conflicts of Law.